The Influence of Financial Technology, Financial Self-Efficacy, and Hedonistic Lifestyle on Personal Financial Management of Generation Z in Medan City - Veri Ferdiansyah; Nurbaiti; Imsar (Equity: Jurnal Ekonomi, 2025)
This study aims to examine the influence of financial technology, financial self-efficacy, and a hedonistic lifestyle on personal financial management among Generation Z in Medan City. Generation Z, as digital natives, are highly exposed to technological conveniences that often encourage impulsive consumption and hedonistic tendencies. The rapid growth of financial technology (fintech) has transformed the way individuals manage their finances, creating both opportunities for efficiency and risks of excessive spending. Using a quantitative approach, data were collected from 100 respondents representing Generation Z through questionnaires distributed online. The collected data were analyzed using multiple linear regression techniques with SPSS. The results show that financial technology, financial self-efficacy, and a hedonistic lifestyle each have a positive and significant effect on personal financial management, both partially and simultaneously. Among these, financial technology has the strongest influence, followed by financial self-efficacy and hedonistic lifestyle. The coefficient of determination (R²) value of 0.761 indicates that 76.1% of the variation in personal financial management can be explained by the three independent variables. These findings highlight that while technological advances enhance financial accessibility, strong self-efficacy and awareness are essential to maintain responsible financial behavior amid hedonistic lifestyle pressures.